Voices of survival in the nuclear age. - Paulson, Dennis (Santa Barbara Capra Press, 1986)
These essays, written by more than 125 people, including William F. Buckley Jr., Phyllis Diller, Andrey Sakharov and Pravda editor Viktor Afarasyev, make compelling reading. Sagans introduction outlines the importance of avoiding nuclear war, and each succeeding essay reveals why and how the writer believes the nuclear problem can be solved. Physicist John W. Gofman asserts that good people can be misguided and that Americans and Western Europeans have natural survival instincts. Sakharov and Afarasyev both maintain that the human race must pull together as a team and overcome the nuclear threat. Education in modern technology is essential, says New York Times columnist Flora Lewis, so that we dont have to rely too heavily on the "experts." New York Governor Mario Cuomo adds another voice of optimism in what is perhaps the most succinctand most powerfulessay.
Keywords: Politics